THE IMAGE OF THE BULLFIGHT AND BULLFIGHTER IN 20TH CENTURY SPANISH POETRY: LORCA'S ELEGY LAMENT FOR IGNACIO SÁNCHEZ MEJIAS / 20. YÜZYIL İSPANYOL ŞİİRİNDE BOĞA GÜREŞİ VE MATADOR İMGESİ: LORCA'NIN IGNACIO SÁNCHEZ MEJIAS'A AĞIT ÖRNEĞİ - Ebru Yener GÖKŞENLİ (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The Spanish people worship bulls with the characteristics like aggressiveness, power and fearlessness, and also worship the bullfighters that fight a dual with bulls. The tradition of bullfight defines the basic character of a nation which perceive life as becoming continuously face to face with death. This character makes the Spaniards consider bullfights as a form of art and the possibility of death becomes an inspiration of this deadly art. The famous Spanish poet Federico García Lorca calls as duende, the muse that comes up at the time when the bullfighter come face to face with death. In this study it's aimed to indicate the roots of the Spaniard's affection for bullfighting. As in 20th century Spanish poetry bullfights theme and image of death is cultivated rather frequently, we'll take Lorca's poem Lament for Ignacio Sánchez Mejías as the study object and we'll intend to analyze this elegy in the aspects of Ignacio's bullfighter figure, the expression of death and mourning and also the symbolical images drawn by Lorca.